(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article considers the peculiarities of psychological image in the novel «The Dream» of Mykhailo Kotsiubynsky. Specificity of psychological drawing, identified and analyzed means of characterization of the work.